The Role of Facebook Group Features for Travelers and Tourism Service Providers in Planning a Trip to Bali - Zuraida, Lukia; Suriana, I Putu Koisuki; Ghani, Bima Maula (Jurnal Sosioteknologi, 2024)
Social media has become a major source of inspiration, reference, and decision-making in planning a travel trip. This study aims to determine the influence of Facebook public group features on tourist trip planning decisions and the implications of using this feature on tourism service providers. The data collection was carried out in two ways, the first by providing a list of questions to informants online and the second by conducting semi structured interviews with tourists and tourism service providers who use Facebook public group feature. Data were analyzed using NVivo 12 Pro to identify meaningful patterns. The results show that it is divided into two categories, the point of view of travelers and tourism service providers. It identified four main roles from a traveler's perspective: activeness, sources of information, reviews and recommendations, and weaknesses.Three main roles emerged from the perspective of tourism service providers, including the utilization of interactions' output, threats, weaknesses, and competitive conditions in the field. The patterns of interactions in Facebook public groups demonstrate the findings.